The Impact of Moral Distress on Clinicians Treating Patients during the COVID-19 Pandemic and the Concurrent Armenian War in 2020: Implications for WHO – EMT Teams. (November 2022) - Hartunyunyan, Hakob; Hertelendy, Attila J.; Hart, Alexander; Benham, Todd; Muekhaelyan, Artak; Ciottone, Greg
Abstract : Background/Introduction: Moral distress is a well-described phenomenon in medical providers. It has been linked to mental health deterioration, decreased job satisfaction, and early retirement. No study has been done on the level of moral distress associated with treating patients in simultaneous disasters. Objectives: 1. To learn what is known about the experience of moral distress in frontline health care providers during the COVID-19 pandemic and the concurrent conflict in Armenia during 2020. 2. To determine how WHO EMTs can support their frontline staff experiencing moral distress. Method/Description: A survey was designed to test the moral distress felt by Armenian EMS providers who had cared for both COVID-19 and war casualty patients. This was adapted from the Moral Distress Scale Revised (MDS-R). Results/Outcomes: Of the questions asked, respondents most often responded that they were disturbed by: "Continuing to participate in care for a hopelessly ill or injured person who is being sustained on a ventilator when no one will make a decision to withdraw support" (Mean 2.68/Median 3/Mode 4); and "Initiated extensive life-saving actions when I think they only prolong death" (2.47/3/3), which caused the next most distress to subjects. Conclusion: It is expected that some health care workers in Armenia are likely facing on-going consequences of the moral distress they faced during this unprecedented period of global pandemic and war. Clinics and teams who are more likely to encounter potentially morally distressing events, such as disaster medicine workers, need to address their moral distress mitigation plan by identifying strategies across the continuum of disaster management.